Traumatic Motor Vehicle Accidents of Malaysia: Implications of Illicit Drugs Use - Nasir, Mohamad; Mainul, Haque; Nordin, Simbak (Japan International Cultural Exchange Foundation, 2016)
Objectives: Driving under illicit drugs is one of the public health problems. It may raise the probability of car accidents worldwide. Therefore, this study is conducted to recognize the prevalence of drug users and the factors influence the severity of injury in motor vehicle accidents (MVA).